The impact of work-related risk factors on the development of neck and upper limb pain among low wage hotel housekeepers in Gondar town, Northwest Ethiopia: institution-based cross-sectional study - Sintayehu Daba Wami; Awrajaw Dessie; Daniel Haile Chercos (Environmental Health and Preventive Medicine, 2019)
Abstract Background Musculoskeletal disorders are a major source of disability accounting for considerable economic loss globally. Studies showed that housekeepers suffer from exposure to many high-risk factors for neck and upper limb musculoskeletal disorders. In Ethiopia, little is known and the information is limited in scope about the magnitude of the problem among hotel housekeepers. Therefore, this study aimed to determine the magnitude of the neck and upper limb musculoskeletal disorders and identify the associated risk factors among hotel housekeepers. Methods Institution-based cross-sectional study design was employed from March 1 to May 20, 2017. Systematic random sampling was used to select 422 study participants among the Gondar town hotels, Ethiopia. The standardized Nordic questionnaire for the analysis of musculoskeletal symptoms was used to measure the neck and upper limb musculoskeletal disorders. Bivariate and multivariable binary logistic regression analyses were performed using SPSS version 20. The significance level was obtained at 95% CI and p value ≤ 0.05. Results The overall magnitude of a self-reported neck and upper limb musculoskeletal disorders among hotel housekeepers in the last 12 months was 62.8% (95% CI 58.3, 67.8). The main body areas of concern were neck pain (50.7%), shoulder pain (54%), elbow/forearm (47.2%), and hand/wrist (45.5%). Age, rest break taken, repetitive movement, reaching/overstretching, organization concern for health and safety, and job satisfaction were the risk factors significantly associated with neck and upper limb musculoskeletal disorders. Conclusions A higher proportion of hotel housekeepers were found to be affected by neck and upper limb musculoskeletal disorders in Gondar town. Repetitive movement and reaching/overstretching were strongly associated risk factors with neck and upper limb musculoskeletal disorders. Therefore, ergonomic, organizational and personal measures, which focus on minimizing repetitive movement and awkward working position and facilitating rest break with exercise, are important to tackle neck and upper limb musculoskeletal disorders among hotel housekeepers.